2017
DOI: 10.1080/14680777.2017.1326550
|View full text |Cite
|
Sign up to set email alerts
|

The mediatized border: technologies and affects of migrant reception in the Greek and Italian borders

Abstract: In line with the European self-description of its borders as a space of "humanitarian securitization," this article approaches the border as a network of mediations around migrants and refugees, where emotions of fear and empathy co-exist through digital connectivities-what we call the "mediatized border." Drawing on media, security, and gender studies, we demonstrate how such techno-affective networks are constitutive of (rather than simply complementary to) the border as a hybrid site of both military protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Many accounts revealed that once migrants were in the hand of traffickers, the first thing that happened to them was the deprivation of their mobile phone. Chouliaraki and Musarò’s [39] case study on two of the main border sites of the 2015 migration “crisis”, Italy and Greece, observed how police and national authorities used communication technologies to identify non-authorized migrants before they reached national borders. That is one of the reasons why many refugees mistrusted digital help services even when provided by NGO websites or chats and preferred informal channels and networks [37].…”
Section: Resultsmentioning
confidence: 99%
“…Many accounts revealed that once migrants were in the hand of traffickers, the first thing that happened to them was the deprivation of their mobile phone. Chouliaraki and Musarò’s [39] case study on two of the main border sites of the 2015 migration “crisis”, Italy and Greece, observed how police and national authorities used communication technologies to identify non-authorized migrants before they reached national borders. That is one of the reasons why many refugees mistrusted digital help services even when provided by NGO websites or chats and preferred informal channels and networks [37].…”
Section: Resultsmentioning
confidence: 99%
“…The media portrayals of people crossing the border, through narratives and images of security and salvation, for example, can be understood as representational barriers that construe their identities as ‘desirable’ or ‘undesirable’. This is what Chouliaraki and Musarò (2017) term the ‘narrated’ border, which is part of the wider ‘mediatized border’, intended as a regime of reception characterized by the fusion of caring compassion for and military protection from mobile populations.…”
Section: The Symbolic Dimensions Of Bordering Practicesmentioning
confidence: 99%
“…As we have argued in our empirical description of the European border as a site of both repelling threats and tender-hearted care, ‘instead of simply referring to representing through the media, the mediatization of the border refers, then, to the ways in which the practices, identities and emotions of the border are performed and constituted through media technologies’ (Chouliaraki and Musarò, 2017: 2).…”
Section: The Symbolic Dimensions Of Bordering Practicesmentioning
confidence: 99%
“…Lilie Chouliaraki (2017) similarly points out that the ‘migrant-related selfie’ was a genre of media production that forcefully entered the European media landscape in this period, but came to be ‘remediated’ in mainstream media representations in ways that fitted within, and reinforced, pre-existing media frames about mass migration. Thus, while media platforms have facilitated a merging of representation and self-representation of migrants for European publics, scholars have conceptualized media representations of migrant border crossings as part of a ‘techno-affective’ network of mediations through which the exclusions of the border are publicly ‘narrated’ and ‘performed’ (Chouliaraki and Musarò, 2017: 545). These studies suggest that although self-representations of migrants have become integrated into mainstream media representations in ‘host countries’, the use of social media platforms by migrants does not, in itself, seem to shift established frames of migrants as victims and/or threats in this context.…”
Section: Platform Circulations Of Sentiment About Migrationmentioning
confidence: 99%